Dual solutions for MHD stagnation-point flow of a nanofluid over a stretching surface with induced magneticfield - Sandeep Naramgari; Sulochana C (International Journal of Science and Engineering, 2015)
Present study deals with the buoyancy-driven MHD mixed convection stagnation-point flow, heat and mass transfer of a nanofluid over a non-isothermal stretching sheet in presence of induced magneticfield, radiation, chemical reaction, suction/injection and heat source/sink. The basic governing partial differential equations are reduced to a set of ordinary differential equations by using appropriate similarity transformation. The resulting system is solved numerically by bvp5c Matlab package. Numerical results are validated by comparing with the published results. The influence of non-dimensional governing parameters on velocity, induced magneticfield, temperature and concentration profiles along with coefficient of skin friction, local Nusselt and Sherwood numbers are discussed and presented with the help of graphs and tables. Comparisons are made with the existed studies. Results indicate that dual solutions exists only for certain range of suction/ injection parameter and injection parameter have tendency to enhance the momentum, thermal and concentration boundary layer thickness.